Antibiotic Resistance of Helicobacter pylori Strains Isolated From Pediatric Patients in Southwest China - Li, Juan; Deng, Jianjun; Wang, Zhiling; Li, Hong; Wan, Chaomin (Frontiers in Microbiology, 2021)
The number of antibiotics that are appropriate for Helicobacter pylori eradication in children is limited. Profiling regional or population-specific antibiotic resistance is essential in guiding the H. pylori eradication treatment in children. The aim of this study was to evaluate the antibiotic resistance in H. pylori strains isolated from children and adolescents in Southwest China. Gastric biopsies from 157 pediatric patients with or without previous H. pylori eradication treatment were collected for H. pylori culture. Susceptibility to amoxicillin, clarithromycin, metronidazole, levofloxacin, tetracycline, furazolidone, and rifampicin was determined by E-test or a disk diffusion assay. A total of 87 patients from three ethnic groups (Han/Tibetan/Yi) were H. pylori culture positive (55.4%). The overall resistance rates were 55.2% for clarithromycin, 71.3% for metronidazole, 60.9% for rifampicin, 18.4% for levofloxacin. No isolate was found to be resistant to amoxicillin, tetracycline and furazolidone. Among the 53 treatment-naïve pediatric patients, primary resistance rates to clarithromycin, metronidazole, levofloxacin, and rifampicin were 45.3%, 73.6%, 15.1%, and 60.4%, respectively. Among the 34 treatment-experienced patients, secondary resistance rates to clarithromycin, metronidazole, levofloxacin, and rifampicin were 70.6%, 67.6%, 23.5%, and 61.8%, respectively. Isolates exhibiting simultaneous resistance to clarithromycin and metronidazole were 28.3% and 52.9% among the treatment-naïve and treatment-experienced patients, respectively. In conclusion, among pediatric patients in Southwest China, resistance rates were high for clarithromycin, metronidazole, levofloxacin, and rifampicin, whereas nil resistance was found to amoxicillin, tetracycline and furazolidone. Our data suggest that the standard clarithromycin -based triple therapy should be abandoned as empiric therapy, whereas the bismuth quadruple therapy (bismuth/PPI/ amoxicillin / tetracycline) would be suitable as first-line empiric treatment regimen for this pediatric population. Tetracycline and furazolidone may be considered for treating refractory H. pylori infections in adolescent patients